Vitamin D as a Possible Biomarker for the Development of Diabetic Retinopathy among Libyan Diabetics - Mustafa Younis G. Younis; Naeima M. El-Zalitni; Ahlam Moftah Khalleefa (Journal of Applied Sciences and Clinical Practice)
Background: Vitamin D (VD) is a fat-soluble vitamin produced in the skin through photosynthesis. It plays many important physiological roles, including maintaining bone structure, regulating the immune response, and helping to prevent various health conditions from general fatigue to cancers. VD deficiency (VDD) is a well-known condition diagnosed by low serum 25-hydroxyvitamin D levels. VDD is considered a risk factor for many health issues, including diabetes and its complications such as retinopathy. Aim: The aim of this study was to evaluate the possible role of VD as a biomarker for diabetic retinopathy (DR) and to study the correlations between VDD and other study investigations such as glycosylated hemoglobin and lipid profile. Materials and Methods: The study population was divided into three groups: Group 1 – diabetics with retinopathy “DR” (30 patients), Group 2 – diabetics without retinopathy “non-DR” (30 patients), and Group 3 – nondiabetics “control” (30 subjects). Blood samples were drawn from study subjects to investigate 25-hydroxyvitamin D, hemoglobin A1C (HbA1c), blood glucose, and lipid profile from April 2022 to December 2022. Results: Regarding 25-hydroxyvitamin D3 (25(OH)D3), the difference in means between the groups was statistically highly significant (P < 0.001). The DR group had the lowest mean of 25(OH)D3 (14.7 ± 5.9 ng/mL) when compared to the other two groups – the non-DR group (17.6 ± 5.4 ng/mL) and the control group (22.8 ± 6.6 ng/mL). The mean HbA1c of the diabetic group (8.2% ± 1.6%) and the mean HbA1c of the nondiabetic group (5.5% ±0.5%) were statistically low significant (P < 0.001) compared to the mean of HbA1c of the DR group (9.2% ± 1.2%). The DR group had a mean and standard deviation (SD) of (137.3 ± 62.0 mg/dL) of triglycerides (TGs) which was very significantly lower (P < 0.049) than the means of serum TG of the non-DR group (mean and SD of TG was 170.3 ± 62 mg/dL). The present study’s correlation coefficient results revealed a significant negative (r = −0.388) correlation between VD and HbA1c, indicating that a decrease in 25(OH)D3 levels is associated with an increase in HbA1c levels and that VDD coexisted with elevated HbA1c levels. The other finding indicates a positive correlation (0.261) between serum cholesterol and VD, meaning that elevated levels of VD coexisted with elevated levels of total cholesterol. Conclusion: The findings of our study showed a significant decrease of 25(OH)D3 in the DR group compared to the control. Moreover, the negative correlation between 25(OH)D3 and the HbA1c levels indicated that VDD coexisted with higher HbA1c levels (a sign of poor diabetic control). Higher HbA1c levels are usually accompanied by an increased risk of incidence of DR. Collectively, our findings suggested that low levels of 25(OH)D3 could be used as a proposed future biomarker for the incidence of DR.